A Comparative Study of GPU Computing Techniques: A Review - Keshar, Durgesh Kumar; Kumar, Sanjay; Patle, V.K (International Journal of Computer Sciences and Engineering, 2025)
Nowadays, time is very important in computational field. Today every field in computer science has a huge amount of data, and we need to process data to get valuable information out of it. To reduce the processing time and using of maximum capacity of processor, we divide a large computation problem in to small chunks that is processed by individual processor. Recent microprocessors, becomes possible to utilize the parallelism using multi-cores which support improved SIMD instructions. In this paper we present the GPU based of Parallel Processing architecture, working and its applications for performing fast execution of a task